1997
DOI: 10.1128/aem.63.4.1326-1331.1997
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity through the Looking Glass: Effect of Enrichment Bias

Abstract: The effect of enrichment bias on the diversity of 2,4-dichlorophenoxyacetate (2,4-D)-degrading (2,4-D ؉) bacteria recovered from soil was evaluated by comparing the diversity of isolates obtained by direct plating to the diversity of isolates obtained from 85 liquid batch cultures. By the two methods, a total of 159 isolates were purified from 1 g of soil and divided into populations based on repeated extragenic palindromic sequence PCR (rep-PCR) genomic fingerprints. Approximately 42% of the direct-plating is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(60 citation statements)
references
References 30 publications
4
55
0
1
Order By: Relevance
“…Otherwise, bacteria belonging to phylotype D may need to be associated with soil particles making it difficult to culture them in liquid. Dunbar et al (1997) previously suggested that enrichment without solid support tends to select for bacteria which grow rapidly and as such outcompete slow-growing microorganisms. Also, Breugelmans observed different compositions of linurondegrading cultures enriched in the presence or absence of soil particles from soil originating from the same field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, bacteria belonging to phylotype D may need to be associated with soil particles making it difficult to culture them in liquid. Dunbar et al (1997) previously suggested that enrichment without solid support tends to select for bacteria which grow rapidly and as such outcompete slow-growing microorganisms. Also, Breugelmans observed different compositions of linurondegrading cultures enriched in the presence or absence of soil particles from soil originating from the same field.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial degradation is considered an important mechanism in the dissipation of crop protection products in the environment. Various bacterial strains and consortia that degrade or mineralize crop protection products such as linuron (Dejonghe et al, 2003;Sorensen et al, 2005;Breugelmans et al, 2007;Satsuma, 2010), atrazine (Topp et al, 2000;Rousseaux et al, 2002;Getenga et al, 2009) and isoproturon (Sorensen et al, 2001) or 2,4-dichlorophenoxyacetic acid (Dunbar et al, 1997) have been isolated from pesticide-treated agricultural soils by means of enrichment in suspended cultures in which the pesticide of interest is provided as sole nutrient and/or energy source. However, little is known about the involvement and contribution of these organisms to the in situ degradation of the respective compounds, and concerns exist about the occurrence of biases during the enrichment process.…”
Section: Introductionmentioning
confidence: 99%
“…Although the latter genera were also detected in other ileostoma samples from subject 1, their relative abundance was generally low (< 0.7%; B. van den Bogert et al, unpublished results). The number of obtained Enterococcus isolates might be explained by a cultivation bias resulting from the use of selective media that preferentially allow growth of specific microbial groups and are known to provide a distorted view of bacterial abundances in the original samples (Dunbar et al, 1997; Table 3 and (clockwise) groupings in Fig. S3.…”
Section: Culture-(in)dependent Analysis Of Small Intestinal Streptocomentioning
confidence: 99%
“…This study described as well a succession of different ndo populations responding to different PAH-contaminated environments. However, results from enrichment experiments can introduce a severe bias, as the array of organisms growing under the enrichment conditions defined do not necessarily reflect what occurs in natural environments (Dunbar et al, 1997).…”
Section: Pah Contamination and Ndo Gene Typesmentioning
confidence: 99%